PENGARUH DANA TABARRU’ DAN UJRAH TERHADAP HASIL INVESTASI PADA PERUSAHAAN ASURANSI SYARIAH DI INDONESIA PERIODE 2013-2018 - Reffy Julianti Azhari; Ikin Ainul Yakin (Syar'Insurance: Jurnal Asuransi Syariah, 2019)
The future of sharia insurance in Indonesia is very bright. Rapid economic growth, rising savings rates and the development of the middle class economy bodes well for the Islamic life insurance industry. Sharia life insurance in Indonesia registered in the Financial Services Authority Institute totaling 52 companies. Of the many companies in this study only took 6 (six) companies in the 2013-2018 period. Researchers took in the company PT. Panin Daichi Life, PT. Central Asia Raya Life Insurance, and PT. Life Insurance Manulife Indonesia, PT. AIA Financial, PT. Prudential Life Assurance. In 4 (four) companies have fluctuating report results that are not directly proportional to investment. But the company PT. Sun Life Financial Syariah between funds of Ujrah participants and investment returns always increases. Based on the above background, the formulation of the issue is taken as follows: 1. How is the influence of Tabarru funds' on investment returns in Islamic insurance companies in Indonesia for the period 2013-2018 ?. 2. How is the effect of ujrah on investment returns in sharia insurance companies in Indonesia for the period 2013-2018 ?. 3. How big is the influence of tabarru funds' and ujrah on investment returns in sharia insurance companies in Indonesia for the period 2013-2018? The research objectives are: 1) To determine the effect of Tabarru funds' on investment returns in sharia insurance companies in Indonesia for the period 2013-2018. 2) To find out the effect of ujrah on investment returns in sharia insurance companies in Indonesia for the period 2013-2018. 3) To determine the effect of Tabarru funds' and ujrah on investment returns in sharia insurance companies in Indonesia for the period 2013-2018. The method used in this study is a quantitative method. From the results of the calculation of the simultaneous regression coefficient test (F test) it was concluded that the tabarru funds variable (X1) and the Ujrah variable (X2) simultaneously affect the investment return on Islamic insurance in Indonesia. This can be seen from the simultaneous test (F test), namely the value of Fcount <Ftable (69.945> 3.28) with a significance value of 0.000> 0.05. As the coefficient of determination test (R2) obtained a value of 0.798 which means it can be concluded that the influence of Tabarru funds and Ujrah on investment returns is 79.8% while the remaining 20.2% is influenced by other variables not included in this study.